2022
DOI: 10.1101/2022.03.14.22272325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and immunogenicity of SARS-CoV-2 vaccine MVC-COV1901 in adolescents in Taiwan: A double-blind, randomized, placebo-controlled phase 2 trial

Abstract: Background: MVC-COV1901 is a subunit SARS-CoV-2 vaccine based on the prefusion spike protein S-2P and adjuvanted with CpG 1018 and aluminum hydroxide. Although MVC-COV1901 has been licensed for emergency use for adults in Taiwan, the safety and immunogenicity of MVC-COV1901 in adolescents remained unknown. As young people play an important role in SARS-CoV-2 transmission and epidemiology, a vaccine approved for adolescents and eventually, children, will be important in mitigating the COVID-19 pandemic. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Using a BAU (Binding Antibody Unit) model, it was predicted that vaccine efficacy should be in the range of 80–90% [ 24 ]. MVC-COV1901 is the first COVID-19 vaccine developed in Taiwan to acquire EUA from the Taiwan Food and Drug Administration [ 25 ]. The Phase IV study for this product is ongoing (NCT05097053 and NCT05079633).…”
Section: Prevention For Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Using a BAU (Binding Antibody Unit) model, it was predicted that vaccine efficacy should be in the range of 80–90% [ 24 ]. MVC-COV1901 is the first COVID-19 vaccine developed in Taiwan to acquire EUA from the Taiwan Food and Drug Administration [ 25 ]. The Phase IV study for this product is ongoing (NCT05097053 and NCT05079633).…”
Section: Prevention For Covid-19mentioning
confidence: 99%
“…However, sotrovimab exhibits poor neutralization of Omicron variants, including BA.2 and BA.4/BA.5. [ 25 , 187 , 199 201 ]. Due to resistance of BA.2, the US FDA announced that sotrovimab is no longer authorized for treatment of COVID-19 (Table 3 ) [ 202 ].…”
Section: Treatment Of Covid-19mentioning
confidence: 99%
“…In addition, the vaccine triggers cellular immune responses by promoting IFN-ϒ and IL-4 secreting T-cells [ 184 ]. Results from the phase-II trial from Taiwan and Vietnam showed that the vaccine had good safety profile with no severe adverse events reported [ 185 ]. Phase-I results demonstrated that the vaccine had a robust immune response [ 184 ].…”
Section: Vaccine Candidates Approved Against Sars-cov-2 Infectionmentioning
confidence: 99%
“…In terms of safety, the V-Watch program, launched by the Taiwan Centers for Disease Control to monitor post-marketing safety, reported no serious adverse effects for MVC in 2 million doses administered [10]. Among adolescents, the vaccine was well tolerated and had an immunogenic effect that is non-inferior to that of young adults [11]. For stability, this vaccine can be transported and stored in standard refrigeration temperatures and can, therefore, be easily utilized in low-resource settings [12].…”
Section: Introductionmentioning
confidence: 99%